Novel Insights in Chronic Lymphocytic Leukemia: Are We Getting Closer to Understanding the Pathogenesis of the Disease? - CALIGARIS-CAPPIO, Federico; GHIA, Paolo (Journal of clinical oncology, 2008)
Chronic lymphocytic leukemia (CLL) has unique epidemiologic, biologic, and clinical features. The progressively emerging picture leads us to consider that the critical genes for malignant CLL cells are those regulated by a number of microRNAs revealed by refined cytogenetic and molecular studies, and that the key molecule is the B-cell receptor (BCR). The hypothesis that CLL cells might be selected by some sort of antigenic pressure is strengthened by numerous findings indicating that a BCR-mediated stimulation plays a relevant role in the natural history of the disease and that autoantigens, as well as molecular structures instrumental in eliminating and scavenging apoptotic cells and pathogenic bacteria, may be relevant in triggering and/or facilitating the evolution of CLL. An important question is whether the tiny monoclonal B-cell populations phenotypically similar to CLL (that occur in the peripheral blood of about 3.5% of healthy individuals and are termed monoclonal B lymphocytosis) might be a critical step in the development of CLL. All relevant events of CLL occur in tissues in which a number of cellular and molecular interactions shape a microenvironment conducive to the accumulation of malignant cells and favor the organization of proliferating cells in focal aggregates of variable size that form the pseudofollicular proliferation centers. Given the impact that understanding the pathogenesis of CLL might have on the development of new treatments, the purposes of this review are to discuss whether the novel insights in CLL are leading us closer to understanding the tenet of the disease; to define the emerging new, stimulating questions; and to unfold the major challenges that still need to be addressed.